Analisis Faktor-Faktor yang Mempengaruhi Tingginya Minat Mahasiswa Berinvestasi di Pasar Modal - Kusuma, Deden Iwan (Green Publisher Indonesia, 2025)
This research examines the factors influencing the interest of students from STIE YKPN Yogyakarta, class of 2021-2023, in investing in the capital market. The factors studied include technological ability, motivation, investment knowledge, capital market socialization, investment risks, and pocket money. This study utilizes a descriptive quantitative method with primary data collected through questionnaires distributed to the students of STIE YKPN Yogyakarta, class of 2021-2023. The findings of this research indicate that technological ability and capital market socialization positively influence students’ interest in investing. Investment risks also have a significant impact on the interest in investing. However, motivation, investment knowledge, and pocket money did not show significant effects on students' investment interest. These results suggest that although factors like motivation and knowledge were anticipated to play a larger role, they were not as influential in this context. The study recommends further research expanding the scope to other universities and regions to verify whether these findings hold across different educational backgrounds and locations. Additionally, it suggests including more independent variables and increasing the sample size to achieve more robust results. This research contributes to understanding the various dimensions that shape investment decisions among young adults, particularly students, in the capital market.